Kant's transcendental idealism - Allison, Henry E. (Yale University Press, 2004)
This landmark book is now reissued in a new edition that has been vastly rewritten and updated to respond to recent Kantian literature. It includes a new discussion of the Third Analogy, a greatly expanded discussion of Kant's Paralogisms, and entirely new chapters dealing with Kant's theory of reason, his treatment of theology, and the important Appendix to the Dialectic.